PENGARUH LITERASI KEUANGAN, IMPULSIVE BUYING, DAN PENGENDALIAN DIRI TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS CIPUTRA - Mustikasari, Adellia; Septina, Fanny (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study was conducted with the aim of knowing the effect of financial literacy, impulsive buying, and self-control on the personal financial management of students majoring in Accounting at Ciputra University. This research method uses quantitative methods, the type of data used is primary data. This study uses a non-probability sampling technique method with purposive sampling technique and the research sample has 123 respondents. The data analysis technique uses multiple linear regression analysis using the SPSS version 22 program. The results of this study indicate that financial literacy has a positive effect and has a significant effect on personal financial management. Impulsive buying has a positive effect but does not have a significant effect on personal financial management. Self-control has a positive effect and a significant effect on personal financial management.